2019
DOI: 10.1093/nop/npz063
|View full text |Cite
|
Sign up to set email alerts
|

Management evaluation of metastasis in the brain (MEMBRAIN)—a United Kingdom and Ireland prospective, multicenter observational study

Abstract: Background In recent years an increasing number of patients with cerebral metastasis (CM) have been referred to the neuro-oncology multidisciplinary team (NMDT). Our aim was to obtain a national picture of CM referrals to assess referral volume and quality and factors affecting NMDT decision making. Methods A prospective multicenter cohort study including all adult patients referred to NMDT with 1 or more CM was conducted. Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…These complications often contribute to poor prognosis ( 18 20 ) and serve as common reasons for MDT referrals ( 21 , 22 ). Another important role of MDTs is to facilitate effective and efficient communication among different specialists ( 23 ), shortening the time required for differential diagnosis and therapeutic decision-making ( 24 , 25 ). In our current research, although only the intracranial lesions at the time of initial BM were recorded, it was found that 53.3% of patients experienced upgrades in their intracranial diagnoses following MDT discussions.…”
Section: Discussionmentioning
confidence: 99%
“…These complications often contribute to poor prognosis ( 18 20 ) and serve as common reasons for MDT referrals ( 21 , 22 ). Another important role of MDTs is to facilitate effective and efficient communication among different specialists ( 23 ), shortening the time required for differential diagnosis and therapeutic decision-making ( 24 , 25 ). In our current research, although only the intracranial lesions at the time of initial BM were recorded, it was found that 53.3% of patients experienced upgrades in their intracranial diagnoses following MDT discussions.…”
Section: Discussionmentioning
confidence: 99%
“…malignant melanoma. This has led to BM occupying substantially more of the neurosurgery, radiology, and oncology workload compared to other brain tumors in recent years (1).…”
Section: Introductionmentioning
confidence: 99%
“…Incidence increases with age and varies with the primary, being most common in non-small-cell lung cancer, breast cancer, and malignant melanoma. This has led to BM occupying substantially more of the neurosurgery, radiology, and oncology workload compared to other brain tumors in recent years ( 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Prognosis and thus decision support for treatment remains partially defined with considerable variation amongst cancer types and molecular features, systemic manifestations, and treatment tolerance 8,10 . Prognostic factors include age, performance status, extra-cranial metastases, treatment history and most importantly the extent of primary disease control 1,9,11,12 .…”
Section: Introductionmentioning
confidence: 99%